Analisis Puisi Sajak Suara Karya Wiji Thukul : Pendekatan Struktural - Budi Hartono; Masnita Massaguni (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2025)
This article discusses the poem “Sajak Suara” by Wiji Thukul through a structural approach that emphasizes the analysis of intrinsic elements of the text, such as diction, imagery, figurative language, typography, and the poem’s inner structure. This poem was chosen because it contains a strong ideological message related to the struggle against oppression and the silencing of freedom of expression, particularly in the context of the New Order regime. The analysis shows that the poem’s formal structure both in form and content, actively reinforces the spirit of resistance and freedom. The use of direct diction, rhetorical language, and free typography reflects an expression of tension and determination. Thus, the structural approach is able to reveal how the poem’s form itself becomes a crucial instrument in conveying socio-political messages. This study is expected to broaden appreciation of poetry as a medium of critique and collective awareness.